Production of Granular Potassium Fertilizer from Oil Palm Empty Fruit Bunch (EFB) Incineration Ash - Erizal, Erizal; Irwan, Irwan; Zaini, Halim (Jurnal Teknologi, 2025)
The transformation of oil palm empty fruit bunch (EFB) incineration ash into granular potassium fertilizer offers a promising approach to recycling agro-industrial waste while producing value-added products. This study focuses on the formulation of EFB ash-based granules using tapioca starch as a natural binder, and examines the effects of binder weight and drying time on granule yield, pH, K₂O content, and moisture content. Tapioca starch was incorporated at five  different weight (5, 10, 15, 20,  and 25 g) to evaluate its influence on granulation performance. The results showed that increasing tapioca starch content significantly improved the granule yield, achieving a maximum of 67.91% at 15 g. However, there are no granular formed. The granular formed at weight of binder 25 g that resulted 67.22% yield and 36.72% Potasium. The pH of the granules slightly decreased with increasing binder dosage. Moisture content was influenced by both the binder weight and drying time; higher starch content retained more water. This study demonstrates that tapioca starch is a viable biodegradable binder for producing eco-friendly granular fertilizers from EFB ash, supporting sustainable waste valorization and agricultural practices.